2020
DOI: 10.1007/s43152-020-00005-w
|View full text |Cite
|
Sign up to set email alerts
|

Using Tools in Mechanobiology to Repair Tendons

Abstract: Purpose of Review The purpose of this review is to describe the mechanobiological mechanisms of tendon repair as well as outline current and emerging tools in mechanobiology that might be useful for improving tendon healing and regeneration. Over 30 million musculoskeletal injuries are reported in the US per year and nearly 50% involve soft tissue injuries to tendons and ligaments. Yet current therapeutic strategies for treating tendon injuries are not always successful in regenerating and returning function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…40 Future studies could investigate the role of acute or repetitive loading on attachment damage and tear propagation by modulating muscle loading and attachment mechanobiology (e.g., treadmill running or muscle stimulation). 41 Although we observed that the duration of injury affected healing outcomes more so than defect size, defect size lead to several differences in gross morphology, bone properties, cellularity, and attachment structure. Rotator cuff tears commonly lead to fibrosis and neovascularization, 19,24 and, in this study, we similarly observed a qualitative increase in fibrotic tissue and vessel formation with increased defect size.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…40 Future studies could investigate the role of acute or repetitive loading on attachment damage and tear propagation by modulating muscle loading and attachment mechanobiology (e.g., treadmill running or muscle stimulation). 41 Although we observed that the duration of injury affected healing outcomes more so than defect size, defect size lead to several differences in gross morphology, bone properties, cellularity, and attachment structure. Rotator cuff tears commonly lead to fibrosis and neovascularization, 19,24 and, in this study, we similarly observed a qualitative increase in fibrotic tissue and vessel formation with increased defect size.…”
Section: Discussionmentioning
confidence: 68%
“…Nuclear aspect ratio (nAR) has been used previously as read out of mechanical force transmission experienced by cells, and changes in nuclear shape can trigger epigenetic changes and influence gene expression. 41,42,45,46 Previous studies have shown that tendon injury leads to an acute decrease in nAR compared to healthy tendons and that nAR increases with increased healing duration, indicating a mechanobiological response to injury and healing. 42 Interestingly, in this study, we observed changes in nAR of local fibroblasts that was dependent on injury size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation